Development of High Yielding Deep Water Rice Variety BRRI dhan91 for Semi Deep Flooded Ecosystem of Bangladesh (Bangladesh Rice Journal, 2020)
Deep water rice ecosystem represents the flood-prone rice ecosystem where rice plant requires elongation ability to reach the surface with a certain amount of plant height to withstand in stagnant flood water condition. Low yield potentiality of locally adapted deep water cultivars limits the total rice production in the country. In present study, efforts were made to evaluate the suitability and adaptability of newly developed high yielding deep water breeding line BR10230-15-27-7B and control variety Fulkori under semi deep water ecosystem of farmer’s field condition in three consecutive years. At six locations, water depth varied from 60 to 140 cm under semi deep water ecosystem. In 2016 and 2017, mean yield of the line ranged between 2.9 to 3.1 t ha-1 while 1.7 t ha-1 for the local control variety Fulkori. However, around 1.0 t/ha yield advantage was found for the newly developed breeding line. Thus, the higher yield potentiality of the breeding line under 140 cm water depth conditions suggested its suitability under shallow flooded environments. During final evaluation in 2018, larger variation was observed in terms of grain yield ranging from 1.1 to 3.8 t ha-1 for the line while 0.4 to 1.7 t ha-1 for the control variety when evaluated under actual deep water areas. This result also supported that this line have greater potentiality under shallow flooded condition. In addition, the breeding line exhibited similar plant height with at least six days earliness compared to the control variety. Finally, National Seed Board (NSB) approved this line as variety and designated as BRRI dhan91 for broadcast Aman (B. Aman) season. In future, this new rice variety could help the local rice growers to cultivate modern high yielding rice variety in shallow flooded environments. BRRI dhan91 also showed better performance for tallness with lodging tolerance, submergence tolerance and moderate elongation ability under shallow flooded conditions.Bangladesh Rice j. 2019, 23(1): 57-63